Is Near-Infrared Spectroscopy a Reliable Method to Evaluate Clamping Ischemia during Carotid Surgery? - Luciano Pedrini; Filippo Magnoni; Luigi Sensi; Emilio Pisano; Maria Sandra Ballestrazzi; Maria Rosaria Cirelli; Alessandro Pilato (Stroke Research and Treatment)
Guidelines do not include cerebral oximetry among monitoring for carotid endarterectomy (CEA). The purpose of this study was to evaluate the reliability of near-infrared spectroscopy (NIRS) in the detection of clamping ischemia and in the prevention of clamping-related neurologic deficits using, as a cutoff for shunting, a 20% regional cerebral oxygen saturation (rSO2) decrease if persistent more than 4 minutes, otherwise a 25% rSO2 decrease. Bilateral rSO2 was monitored continuously in patients undergoing CEA under general anesthesia (GA). Data was recorded after clamping, declamping, during shunting and lowest values achieved. Preoperative neurologic, CT-scan, and vascular lesions were recorded. We reviewed 473 cases: 305 males (64.5%) mean age 73.3±7.3. Three patients presented transient ischemic deficits at awakening, no perioperative stroke or death; 41 (8.7%) required shunting: 30 based on the initial rSO2 value and 11 due to a decrease during surgery. Using the ROC curve analysis we found, for a >25% reduction from baseline value, a sensitivity of 100% and a specificity of 90.6%. Reliability, PPV, and NPV were 95.38%, 9%, and 100%, respectively. In conclusion, this study indicates the potential reliability of NIRS monitoring during CEA under GA, using a cutoff of 25% or a cutoff of 20% for prolonged hypoperfusion.